8(19) molecular knot: a theoretical analysis of the electronic structure using an ONIOM approach - Morgon, Nelson H.; Souza, Aguinaldo R. de [UNESP] (Springer, 2021)
The present work analyzes the electronic and molecular properties of the 8(19) ([Fe(II)(4)]Cl) and metal-free knot ligand complexes obtained from X-ray crystal structure of molecular 8(19) knot complex [Fe(II)(4)(PF6)(7)]Cl. The studies were theoretically investigated by means of DFT, TD-DFT, and ONIOM approaches. Basis sets functions from all-electron calculations for bromine, iodine, and iron atoms were adapted to be used along with relativistic effective core potential, while H, C, N, O, and Cl atoms were described by Pople basis sets. The diffusion effect of halogen into the 8(19) cavity, UV-Vis, and Electronic Circular Dichroism spectra were also analyzed. All calculations were performed using solvent effect through the SCRF/SMD model and dispersion effects by Grimme methodology. The value of mean separation distance between Cl and iron atom (7.218 angstrom) is in good agreement with X-ray experimental result (7.258 angstrom). Circular dichroism spectrum of metal-free 8(19) knot ligand was calculated and the maximum absorption in 262 nm, Delta epsilon; obtained was 67 L mol(- 1) cm(- 1). These results are qualitatively similar to those obtained experimentally, 295 nm and 80 L mol(- 1) cm(- 1), respectively. In this study, we report the electronic and molecular properties of the 8(19) ([Fe(II)(4)]Cl and metal-free knot ligand complexes and compare with the results obtained from X-ray crystallographic data of 8(19) knot complex [Fe(II)(4)(PF6)(7)]Cl. The 8(19) knot were investigated by means of DFT, TD-DFT, and ONIOM approaches. Basis sets functions from all-electron for Br, I, and Fe atoms were adapted to be used along with relativistic effective core potential, while H, C, N, O, and Cl atoms were described by Pople basis sets. The objective was to understand the stability of the 8(19) knot as a function of the substitution of the central halogen atom (Cl), and the signal in the circular dichroism spectra. From the equilibrium geometries, we have obtained good results for values of the bond distance, bond angle, and dihedral angle along the molecular structure when these variables are compared with the results obtained from X-ray data. The diffusion effect of halogen into the 8(19) cavity, UV-Vis, and Electronic Circular Dichroism spectra was also analyzed. Circular dichroism spectrum of metal-free 8(19) knot ligand was calculated, and the maximum absorption is in good agreement with the experimental value. The ONIOM methodology combined with the relativistic effective core potential and the atomic basis sets provide good results for systems with a complex topology, such as knots.
Keywords: 8(19) knot; ONIOM; Relativistic core potential; Topology